American soldiers in Iraq McSoldiers or innovative professionals - Ender, Morten G. 1960- (Routledge, 2009)
"American Soldiers in Iraq offers a unique sociological snapshot of American soldiers in Iraq, analyzing their collective narratives in relation to the military sociology tradition"--Provided by publisher